The Effect of Accounting Information Quality and Financial Self-Efficacy on Financial Management Behavior with Love of Money as A Moderating Variable - Irham Pakawaru; Muhammad Syafaat; Anees Janee Ali (Universitas Negeri Malang, 2026)
The increasing use of technology in business activities has the potential to drive higher consumerist behavior, especially when business actors have limited financial literacy and inadequate financial management skills, particularly in investment decision-making. This study aims to examine the effect of accounting information quality and financial self-efficacy on financial management behavior, with love of money as a moderating variable. This study uses a quantitative approach with a survey method targeting micro, small, and medium enterprise (MSMEs) owners spread across Palu City, Donggala Regency, and Sigi Regency. The final sample of the study consisted of 100 respondents determined through purposive sampling technique. The data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The results of the study indicate that accounting information quality, financial self-efficacy, and love of money have a significant effect on financial management behavior. However, the moderation test results show that love of money does not moderate the relationship between accounting information quality and financial management behavior. Conversely, love of money is proven to moderate the relationship between financial self-efficacy and financial management behavior in a negative direction, thereby weakening the relationship. These findings support the Theory of Planned Behavior, which emphasizes the importance of accounting information quality and individuals’ belief in their ability to manage finances to improve the financial management behavior of MSMEs